Sulfonamides as multifunctional agents for Alzheimer's disease. Issue 3 (1st February 2015) - Bag, Seema; Tulsan, Rekha; Sood, Abha; Cho, Hyejin; Redjeb, Hana; Zhou, Weihong; LeVine, Harry; Török, Béla; Török, Marianna
Graphical abstract